The Influence Of Class Iii Inpatient Sanitation On Patient Satisfaction At Bhayangkara Hospital Tk. Iii Nganjuk - Sumiati; Ukik Agustina; Wahyu Purnomo Jati (Journal of Hospital Management and Services, 2023)
Sometimes it is very ironic, where hospitals or health centers do not maintain the cleanliness of health service facilities. Cleanliness of health service facilities is an indicator of service quality that can influence patient satisfaction. The aim of the research is to analyze the effect of class III inpatient sanitation on patient satisfaction at Bhayangkara Tk Hospital. III Nganjuk. This research uses a quantitative design with a cross sectional approach. The population was 80 patients with a sample of 67 respondents using purposive sampling technique. The independent variable is class III inpatient room sanitation and the dependent variable is patient satisfaction. Data were collected using a questionnaire instrument and analyzed by the Chi-Square test. The research results showed that almost all (88%) had an assessment of the sanitation of class III inpatient rooms in the clean category, namely 59 respondents. Patient satisfaction shows that the majority (73%) have a level of satisfaction in the very satisfied category, namely 59 respondents. Chi Square test results on the effect of class III inpatient sanitation on patient satisfaction at Bhayangkara Tk Hospital. III Nganjuk has a significant value (p) of 0.000 < 0.05, which means that there is an influence of class III inpatient sanitation on patient satisfaction at Bhayangkara Tk Hospital. III Nganjuk. It is hoped that Bhayangkara Hospital Tk. III Nganjuk can further improve environmental cleanliness because the cleaner the inpatient room, the more patient satisfaction with the quality of service will increase.